Método de teologia da libertação em debate: a perspectiva de Clodovis Boff - Junges, Fábio César (2011)
This dissertation is about the theological-methodological production of Clodovis Boff. Through a historic-descriptive analysis, it synthesizes the theological production of the author in three phases. The systematization is done from the image of two undulations, supported and enabled by a starting point, corresponding also to the three chapters of the dissertation. The main research problem came from the methodological problem of the Liberation Theology (TdL) as said by the own C. Boff in his newest texts, needing revision, reformulation and epistemological redefinition. In the first chapter is showed the start point of C. Boff theological-methodological reflection. The discussion starts from the TdL‟s methodology in the seventies, as done and characterized by the author. From his point of view, named regency and urgency scheme, comes the problem and the objective investigation to C. Boff doctorate theses, to kwon, difficulties on the methodological articulation of the Latin American‟s theology. So, the developed argumentation in the first chapter is the basis to further discussion, and start point to all the reflection. On the second chapter, named optimal- radical undulation, before present the new articulation of the TdL, are collected historic elements to generate conditions to new problems. After that, are done conceptualization clarifications of theological items and elements, besides the methodological articulation of this second phase. All the reflection ends with the confront of the theses and methodological conclusions of both phases, while comparing the differences and equalities of them. The third chapter and phase of C. Boff‟s production, named critical-renewed undulation, besides to describe his theological-methodological thoughts, make some reviews to C. Boff, while resumption the main questions of the debate advocated by the author in his newest texts. The try is to make visible new methodological conditions to the TdL. Thus, the present research finds the C. Boff concern, although with new assumptions.